A case of recurrence of hepatocellular carcinoma 5 years after liver transplantation - YOSHIZUMI, Tomoharu; KAJIWARA, Yuichiro; IKEGAMI, Toru; MAEHARA, Yoshihiko; SHIRABE, Ken (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2012)
Liver transplantation (LT) has become a choice for hepatocellular carcinoma (HCC) within certain criteria. Despite the considerable recurrent free survival rate after LT for HCC, its recurrent presentation usually carries a very poor prognosis. The recurrence of HCC after LT is usually characterized by early recurrence within 2 years, presenting disseminated systemic disease. In this report, we present a case of recurrent HCC after a lapse of 5 years following living donor liver transplantation (LDLT) for HCC. The case involved a male in his sixties, performed LDLT for HCC outside the Milan criteria. The patient had had uneventful post-transplant course with stable liver function until the recurrent disease occurred 5 years after LDLT. It presented with lymph node metastasis in the lesser omentum of the gastric lesser curvature. The tumor was removed. The patient had another metastasis in the liver graft 5 months after the surgery, and received chemo-radiation therapy. However, he was expired from the uncontrolled recurrent disease 5 years and 7 months after LDLT.